METODE COST PLUS PRICING DENGAN PENDEKATAN FULL COSTING MAMPU MENENTUKAN HARGA JUAL (Studi Kasus Pada CV Karya Dharma) - Abdul Latief R (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
Highlights of this study is to determine the calculation of the cost of production and selling price setting process at CV. Karya Dharma. Degan production cost price calculation using a full costing method and setting the selling price using a cost plus pricing. The method used is quantitative research methods. Based on the characteristics of the issues raised by the researchers, the study is classified as a quantitative descriptive research. The data used in this study are primary data obtained from interviews with the company. And secondary data obtained from data on costs of From the analysis of the data, the results showed that the company's calculation of the cost of production is lower than the production cost price calculation using a full costing method. While using the cost plus pricing method with a mark-up, the selling price is lower than according to the company.